Swallowing-related muscle inflammation and fibrosis induced by a single dose of radiation exposure in mice - Shuntaro Soejima; Chia-Hsien Wu; Haruna Matsuse; Mariko Terakado; Shinji Okano; Tsuyoshi Inoue; Yoshihiko Kumai (Laboratory Animal Research)
Abstract Background Although radiotherapy is commonly used to treat head and neck cancer, it may lead to radiation-associated dysphagia (RAD). There are various causes of RAD, however, the mechanism has not yet been fully identified. Currently, the only effective treatment for RAD is rehabilitation. Additionally, there are few available animal models of RAD, necessitating the development of new models to establish and evaluate RAD treatments. We hypothesize that radiation-induced neck muscle fibrosis could be one of the causes of RAD due to impairment of laryngeal elevation. Therefore, in this study, we focused on the changes in inflammation and fibrosis of the strap muscles (Sternohyoid, Sternothyroid, and Thyrohyoid muscles) after a single-dose irradiation. This research aims to provide a reference animal model for future studies on RAD. Results Compared to control mice, those treated with 20-Gy, but not 6.7-Gy, irradiation had significantly increased tumor necrosis factor-α (TNF-α) (p < 0.01) and α-smooth muscle actin (αSMA) (p < 0.05) expression at 10 days and significantly increased expression levels of motif chemokine ligand-2 (CCL2), α-SMA, tumor growth factor-β1 (TGF-β1), type1 collagen, and interleukin-1β (IL-1β) (p < 0.05) in the muscles at 1 month by real-time PCR analysis. The results of immunohistochemistry showed that the deposition of type 1 collagen gradually increased in extracellular space after radiation exposure, and the positive area was significantly increased at 3 months compared to non-irradiated control. Conclusions A single dose of 20-Gy irradiation induced significant inflammation and fibrosis in the strap muscles of mice at 1 month, with immunohistochemical changes becoming evident at 3 months. This cervical irradiation-induced fibrosis model holds potential for establishing an animal model for RAD in future studies. Level of evidence N/A.